2022
DOI: 10.1177/1934578x221096966
|View full text |Cite
|
Sign up to set email alerts
|

Jiedu Huoxue Decoction for Cytokine Storm and Thrombosis in Severe COVID-19: A Combined Bioinformatics and Computational Chemistry Approach

Abstract: Jiedu Huoxue Decoction (JHD), a recommended traditional prescription for patients with severe COVID-19, has appeared in the treatment protocols in China. Based on bioinformatics and computational chemistry methods, including molecular docking, molecular dynamics (MD) simulation, and Molecular Mechanics Generalized Born Surface Area (MM/GBSA) calculation, we aimed to reveal the mechanism of JHD in treating severe COVID-19. The compounds in JHD were obtained and screened on TCMSP, SwissADME, and ADMETLab platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The molecular docking studies confirmed that the conformations of the puerarin-ACE2, quercetin-EGFR, luteolin-EGFR, and quercetin-IL1B complexes were stable, and thus JHD could treat COVID-19 by intervening in cytokine storm, thrombosis, and the entry of SARS-CoV-2, while regulating the immune system. 3 The rich diversity of African medicinal plants and their chemical compounds with antiviral, anti-inflammatory, and immunomodulatory activities, and COVID-19 symptom relieving effects has been reviewed by Akindele toxicity, and chemical components of 9 plants (Bryophyllum pinnatum, Aframomum melegueta, Garcinia kola, Sphenocentrum jollyanum, Adansonia digitata, Sutherlandia frutescens, Hibiscus sabdariffa, Moringa oleifera, and Nigella sativa), making them potential candidates for further investigation for effectiveness against COVID-19. 4 In another review by Sharma et al, the authors have reviewed herbal drugs and their constituents exhibiting antiviral properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular docking studies confirmed that the conformations of the puerarin-ACE2, quercetin-EGFR, luteolin-EGFR, and quercetin-IL1B complexes were stable, and thus JHD could treat COVID-19 by intervening in cytokine storm, thrombosis, and the entry of SARS-CoV-2, while regulating the immune system. 3 The rich diversity of African medicinal plants and their chemical compounds with antiviral, anti-inflammatory, and immunomodulatory activities, and COVID-19 symptom relieving effects has been reviewed by Akindele toxicity, and chemical components of 9 plants (Bryophyllum pinnatum, Aframomum melegueta, Garcinia kola, Sphenocentrum jollyanum, Adansonia digitata, Sutherlandia frutescens, Hibiscus sabdariffa, Moringa oleifera, and Nigella sativa), making them potential candidates for further investigation for effectiveness against COVID-19. 4 In another review by Sharma et al, the authors have reviewed herbal drugs and their constituents exhibiting antiviral properties.…”
mentioning
confidence: 99%
“…The molecular docking studies confirmed that the conformations of the puerarin-ACE2, quercetin-EGFR, luteolin-EGFR, and quercetin-IL1B complexes were stable, and thus JHD could treat COVID-19 by intervening in cytokine storm, thrombosis, and the entry of SARS-CoV-2, while regulating the immune system. 3…”
mentioning
confidence: 99%